Labial Tooth Wear and Culture - Pierre-Francois Puech (Dental Anthropology Association, 1992)
Surface alterations observed on the anterior teeth of prehistoric humans suggest that incisors are involved in many uses related to ingestion, manipulations, and dental care activities. These culture-related uses can be distinguished in dental remains from throughout major periods of human evolution.